2019
DOI: 10.1088/1742-6596/1389/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and critical current of bulk MgB2 superconductor

Abstract: The structure of bulk MgB2 specimens after cold deformation in Bridgeman anvils and “Toroid” chamber and following recovery annealings has been studied by scanning and transmission electron microscopy. It is demonstrated that in spite of the matrix phase grain coarsening by 5-7 times under annealing compared to the as-deformed state, the critical current density increases by a factor of 3 (6.7×104 A/cm2 at 30 K after deformation in the “Toroid” chamber and recovery annealing).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…From the literature review [1][2][3][4][5][6][7][8][9][10][11][12], it can be inferred that the thermal decomposition of MgB 2 starts around 830 • C. We performed conventional SPS experiments at 100 MPa with a dwell time of 5 min and observed that thermal decomposition appeared at 1050 • C. The shift of this thermal decomposition to a higher temperature can be attributed to the benefit of 100 MPa pressure under pulse electric current. We further observed by conventional SPS that when the applied pressure was increased, the crystallite size decreased at 950 • C, as shown below.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…From the literature review [1][2][3][4][5][6][7][8][9][10][11][12], it can be inferred that the thermal decomposition of MgB 2 starts around 830 • C. We performed conventional SPS experiments at 100 MPa with a dwell time of 5 min and observed that thermal decomposition appeared at 1050 • C. The shift of this thermal decomposition to a higher temperature can be attributed to the benefit of 100 MPa pressure under pulse electric current. We further observed by conventional SPS that when the applied pressure was increased, the crystallite size decreased at 950 • C, as shown below.…”
Section: Resultsmentioning
confidence: 98%
“…Various research teams reported on employing recent techniques such as field-assisted sintering or high-pressure-assisted sintering techniques [8][9][10][11][12] to obtain MgB 2 dense compact samples with relative densities greater than 95%, in comparison with other conventional pressureless sintering techniques. The influence of the sintering parameters in field-assisted sintering, such as pressure, dwell time, temperature, and heating/cooling rate, on the structural, microstructural, and superconducting properties of MgB 2 have been studied [8][9][10][11][12]. An increase in the relative density of MgB 2 up to 99% was achieved when the sintering temperatures were in the range of 900-1050 • C [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations